A study of the impact of Internet use on the employment transition of rural labor: evidence from China - Yuan, Ruolan; Fu, Qin (Frontiers in Sustainable Food Systems, 2025)
IntroductionAmid the rapid development of the digital economy, the digital economy centered on Internet technology is reshaping the employment structure, particularly exerting significant influences on rural economic transformation and the upgrading of employment.MethodsThis paper empirically analyzes the impact of Internet usage on the employment transition of the rural labor force by employing the 2010–2020 China Family Tracking Survey panel data (CFPS).Results and discussionStudies show that the use of the Internet has a significant positive effect on the employment transformation of rural labor force and helps promote the transformation of rural labor force from agricultural employment to non-agricultural employment. The mechanism analysis discovers that Internet usage further affects the employment transition of the rural labor force by influencing social capital and information channels. The heterogeneity analysis indicates that different types of Internet usage have positive effects on the employment transition of the rural labor force, and Internet usage has positive effects on the employment transition of the “middle-aged generation,” “new generation” and “high-skilled” rural labor force. Simultaneously, Internet usage has a more pronounced effect on the employment transition of the “middle-aged generation,” “new generation” and “highly skilled” rural labor force. The expanded analyses demonstrate that the use of the Internet facilitates the deepening of the internal transition of the labor force from informal to formal employment, and also promotes engagement in manufacturing, transportation, wholesale, education and catering, while inhibiting agriculture, forestry, animal husbandry and fishery, and the construction industry. Based on the above findings, this paper proposes corresponding policy recommendations for promoting the construction of digital villages and enhancing the employment of the rural labor force.